Intercropping sugar cane - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A multidisciplinary approach to food production and farrning has demonstrated how intercropping of sugar cane can have beneficial effects on the nutrition of cane farmers and their families, and on the yields of cane also. A team of researchers in...